2000
DOI: 10.1606/1044-3894.1018
|View full text |Cite
|
Sign up to set email alerts
|

Confidentiality in Direct Social-Work Practice: Inevitable Challenges and Ethical Dilemmas

Abstract: Social workers have long concerned themselves with confidentiality and its importance to practice. In 1922, social workers created theirCode of Ethics, a major precept of which is the protection of confidentiality, defined as the regulation, both legal and ethical, that protects the client's rights of privacy. Social workers are confronting many ethical issues related to confidentiality, such as increasing demands for accountability, mandated duty-to-protect or -warn provisions, expanding court involvement in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The results of this study show that there was some consensus among school counselors with regard to breaking confidentiality to report suicidal ideation, but there was much less consensus with the other risk-taking behaviors. However, ethical decisions must be made on a daily basis and the most ambiguous or most difficult areas may be the ones that we are forced to navigate the majority of the time (Millstein, 2000). For example, self-mutilation is becoming a more common behavior observed in schools (White Kress et al, 2006), yet the counselors in our sample didn't agree on how to respond to this behavior.…”
Section: Resultsmentioning
confidence: 94%
“…The results of this study show that there was some consensus among school counselors with regard to breaking confidentiality to report suicidal ideation, but there was much less consensus with the other risk-taking behaviors. However, ethical decisions must be made on a daily basis and the most ambiguous or most difficult areas may be the ones that we are forced to navigate the majority of the time (Millstein, 2000). For example, self-mutilation is becoming a more common behavior observed in schools (White Kress et al, 2006), yet the counselors in our sample didn't agree on how to respond to this behavior.…”
Section: Resultsmentioning
confidence: 94%
“…In general, confidentiality has been defined as the legal and ethical regulations that protect either the research participants or the clients in terms of their rights to privacy (Millstein, 2000). Ethical dilemmas center on conflicts between the rights of the individual to privacy versus the rights of the larger community to have access to the client's private information.…”
Section: Ethics In Social Work Practice and Researchmentioning
confidence: 99%
“…In direct practice, such conflicts are evident in the dilemmas about writing and protecting case records, in sharing confidential information for purposes of referral or consultation, in following mandates regarding duty-to-warn or duty-toprotect, and when there is court involvement such as in child welfare cases and adoption (Millstein, 2000;Palmer & Kaufman, 2003;Reamer & Siegel, 2007;Saxon, Jacinto, & Dziegielewski, 2006). Yet Millstein's (2000) study of 372 direct practice MSWs suggested "there is a gap" (p. 278) between what clinicians understand to be their ethical obligations and what they actually do in practice, particularly regarding confidentiality. More than one half the respondents in Millstein's study reported they did not have clients sign consent forms prior to the release of confidential clinical information to other professionals.…”
Section: Ethics In Social Work Practice and Researchmentioning
confidence: 99%
“…They imprecise about explanation and implication inherent in the principles to be translated into practice; practitioners often do not employ the ethical code during practice and practice is mostly directed by administrative processes and law making the code superfluous (Reamer and Shardlow, 2009;Millstein, 2000;Clark, 1999). Researchers have explicated that practitioners are apt to create choices relying on technical aspects contained by job description than centring it on Code of Ethics' principles and values; only an insignificant figure of practitioners (15.9%) consulted to the code to solve ethical dilemma; ensuing legal regulation adherence make practitioners to perform incongruity to the code (Kugelman, 1992;Millstein, 2000;Reamer, 2005).…”
Section: Introduction and Background Of The Studymentioning
confidence: 99%